Description of the COVID-19 Incident Based on Regional and Individual Characteristics (Case Study in Sleman Regency in The First Year of the Pandemic) - Ariyani, Novia; Sunarti, Sunarti; Sukesi, Tri Wahyuni (Universitas Teuku Umar, 2024)
COVID-19 is a disease caused by the SAR virus, which can be transmitted from human to human and, in severe cases, lead to fatalities. Sleman Regency holds the highest number of COVID-19 cases in the Special Region of Yogyakarta (DIY). This research aims to describe characteristic regions and individual COVID incidents in Sleman regency during the first year of the pandemic period. Region’s characteristic is observed based on population density, even though the individual characteristic includes age, gender, and mobility. This descriptive research methodology relies on secondary data reports on COVID-19 cases in Sleman District Health Service. The research result showed COVID incidents in the first year of the pandemic is dominated by regions with population density. The highest case in Depok is as much as 18.4%. COVID cases in males in the age group 31-45 years old were 14.4%. The productive ages group also had a prevalence higher than 25.7%. In summary, the highest number of COVID-19 cases in the region with high population density, on male gender and productive age additionally the asymptomatic symptom group.